Can Psychological Traits Explain Mobility Behavior During the COVID-19 Pandemic?. Issue 6 (August 2021) - Chan, Ho Fai; Moon, Jordan W.; Savage, David A.; Skali, Ahmed; Torgler, Benno; Whyte, Stephen
The current COVID-19 pandemic is a global, exogenous shock, impacting individuals' decision making and behavior allowing researchers to test theories of personality by exploring how traits, in conjunction with individual and societal differences, affect compliance and cooperation. Study 1 used Google mobility data and nation-level personality data from 31 countries, both before and after region-specific legislative interventions, finding that agreeable nations are most consistently compliant with mobility restrictions. Study 2 ( N = 105, 857) replicated these findings using individual-level data, showing that several personality traits predict sheltering in place behavior, but extraverts are especially likely to remain mobile. Overall, our analyses reveal robust relationships between traits and regulatory compliance (mobility behavior), both before and after region-specific legislative interventions, and the global declaration of the pandemic. Further, we find significant effects on reasons for leaving home, as well as age and gender differences, particularly relating to female agreeableness for previous and future social mobility behaviors. These sex differences, however, are only visible for those living in households with two or more people, suggesting that such findings may be driven by division of labor.